About the Status and Prospects of Gerontology and Geriatrics in the Kyrgyz Republic (Indian Journal of Forensic Medicine & Toxicology, 2020)
The objective is to assess the state and prospects of development of the gerontological service and to studythe level of the demographic situation in the Kyrgyz Republic.We studied Legislative, regulatory and legal documents and materials from open sources have studied sinceUsing the example of Bishkek and Nizhne-Serafimovsk social stationary facilities, the state of healthwas analyzed, and 442 patients examined. Successes in the development of the gerontology: the KyrgyzRepublic became a member of the AgeNet International gerontological network (2005), the law “On SeniorCitizens in the Kyrgyz Republic” (2011) was adopted, and an Action Plan to improve the quality of life ofolder citizens at 2019-2025. A high frequency of comorbidity revealed: 241 (56.4%) of the wards had from1 to 3 diseases, 185 (43.3%) from 4 to 6 diseases and in 128 (29.9%) of the departments, seven or morediseases registered. The country needs to create a single coordinating body for gerontological and geriatricservices, which will be responsible for its work and development.